New species of the deep-sea munnopsid genus Tytthocope (Crustacea, Isopoda, Asellota) from the South Atlantic and the Southern Ocean - Malyutina, Marina V.; Brandt, Angelika (Zootaxa, 2014)
In the benthic samples collected during the deep-sea expeditions ANDEEP from the Weddell Sea and DIVA from the Argentine Basin the isopod family Munnopsidae was the most specious and numerous. Among the collected munnopsids three new species of Tytthocope Wilson & Hessler, 1981 have been discovered. Tytthocope is one of six genera of the subfamily Eurycopinae. It differs from other genera of the Eurycopinae by having a strongly reduced pereonite 7 and inflated pleotelson. Until now the genus consisted of five described species: four of them are known from the northern Atlantic and only one species, T. sulcifrons (Barnard, 1920) was described from the southern Atlantic off the South Africa coast. The five known species of Tytthocope have been recorded from depths less than 1461 m. Descriptions of three new species of Tytthocope collected in the South Atlantic and Southern Ocean at depths between 1530–4608 m, T. divae sp. nov., T. fahrbachi sp. nov. and T. longitelson sp. nov. are presented in the paper. T. sulcifrons is redescribed herein based on the type material.